Inside Back Cover: Molecular Chemistry and Engineering of Boron‐Modified Polyorganosilazanes as New Processable and Functional SiBCN Precursors (Chem. Eur. J. 38/2017). Issue 38 (8th May 2017) - Viard, Antoine; Fonblanc, Diane; Schmidt, Marion; Lale, Abhijeet; Salameh, Chrystelle; Soleilhavoup, Anne; Wynn, Mélanie; Champagne, Philippe; Cerneaux, Sophie; Babonneau, Florence; Chollon, Georges; Rossignol, Fabrice; et al.
Abstract : Functional boron‐modified polysilazanes with various Si/B ratios have been synthesized as SiBCN precursors to supply silicoboron carbonitride (SiBCN) ceramics with the desired phase distribution and homogeneity after pyrolysis. This polymer‐derived ceramics (PDCs) route has been demonstrated to allow polymer shaping to produce three dimensional (3D) structures after pyrolysis. Dense parts as well as ceramics with various pore scales have been prepared from these processable polymers. More information can be found in the Full Paper by S. Bernard et al. onpage 9076 .